2020
DOI: 10.12911/22998993/116323
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Windbreak Parameters on the Wind Erosion Risk Assessment in Agricultural Landscape

Abstract: The increasing risk of wind erosion in the context of climate change represents a highly pressing issue. This increase is a result of the growing occurrence of droughts and elevated temperatures in the intensively farmed areas. Effective protection against the wind erosion can be provided by windbreaks, especially during the period when the soil is not protected by the vegetation cover of crops. In this report, the authors wanted to compare the methods defining the windbreak protection zones. The optical poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…They recommended taking into account both the height and optical porosity. Kučera et al [27] concluded that the optical porosity best reflects the effect of one-row windbreaks. In the case of wider windbreaks, parameters for expressing the 3D structure should be developed.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended taking into account both the height and optical porosity. Kučera et al [27] concluded that the optical porosity best reflects the effect of one-row windbreaks. In the case of wider windbreaks, parameters for expressing the 3D structure should be developed.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kucera et al, [19] and Reháek et al [20] found that windbreaks could effectively protect against wind erosion, especially when agricultural plants do not cover the soil. Within the agricultural landscape, windbreaks and other linear constructions reduce wind speed and improve the microclimate within the sheltered zone.…”
Section: Effects Of Windbreaks On Wind Speed Reduction and Soil Prote...mentioning
confidence: 99%
“…Agroforestry systems can improve the soil health of arable systems, as the trees can increase soil organic matter and retain nutrients (Jose et al, 2009). Integrating trees in crop systems can also reduce soil erosion by increasing the permanence of vegetation cover (Jose et al, 2009) and windbreaks and shelterbelts can reduce windspeed (Bartus et al, 2017;Kučera et al, 2020). Trees on arable land can increase rainfall infiltration rates and soil water retention and reduce nitrate leaching (Siriri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%